Acute Severe Liver Injury Related to Long-Term Garcinia cambogia Intake. Issue 8 (11th August 2020) - Ferreira, Victor; Mathieu, Alexandre; Soucy, Geneviève; Giard, Jeanne-Marie; Erard-Poinsot, Domitille
ABSTRACT: Herbal and dietary supplements are frequently used as weight loss supplements. However, they account for 20% of drug-induced liver injury. Garcinia cambogia 's (GC) active compound, hydroxycitric acid, can be found among those supplements. We report a 26-year-old woman who had been taking GC for 7 months when she presented with subacute liver failure and ultimately required a liver transplantation. This report highlights the risk of liver injury after long-term use of GC and demonstrates the importance of considering a close and prolonged monitoring of patients in a tertiary liver transplant center.